Short Tandem Repeat Typing Using Endogenous DNA Isolated from Human Fingernail - Shehab, Miriam Jasim (Al-Nahrain Journal of Science, 2018)
Genomic DNA was isolated from variable biological sources. Nails contain genomic DNA but there is limitation in isolating of genetic material from this tissue due to the special composition and structure of this tissue in which DNA embedded in keratinized cells. This study aimed to investigate the capability of using DNA that isolated from fingernails in forensic analysis. Thirty fingernails clipping were collected from three groups (10 fingernail samples for children, 10 fingernail samples for adolescent and 10 fingernail samples for adult) in addition to thirty buccal swabs collected from the same volunteers as reference samples. Both fingernail clipping and buccal swabs were subjected to DNA extraction using phenol/chloroform extraction. All samples were typed for fifteen autosomal STR loci along with amelogenin, using the Applied Biosystems AmpFiSTR® Identifiler™ kit. Our finding showed that input of 5 mg nail material (1 to 2 of fingernail clippings) gives a variable yield of DNA concentration also there was no significant difference in The mean of concentration for samples that isolated from whole fingernail and those isolated from fingernail after cut into small pieces for children groups while there were significant difference for adult and adolescent groups (0.107702, 0.07544 and 0.000192 respectively). Also the allele’s percentage of STR profiles for three age groups was fluctuated among (100, 33.3, 53.3, 66.6, 73.3, 86.6, and 93.3%).